Implementation of the Think Pair Share (TPS) Learning Model as an Effort to Improve the Arabic Language Essay Writing Ability (Insya) of Grade VIII Students of MTs Zamahsyari - Dwi Ulfiah; Ade Arip Ardiansyah (UIN Sunan Gunung Djati Bandung, 2025)
This research aims to evaluate the application of the Think Pair Share (TPS) learning model as an effort to improve the ability to write essays (insya) in Arabic for class VIII students at MTs Zamahsyari. The research uses the classroom action research (PTK) method which consists of four stages: planning, implementation, observation and reflection. The research subjects were class VIII students who had difficulty writing Arabic essays. Data was collected through writing tests, classroom observations, and interviews with students and teachers. The research results show that the application of the TPS model can improve students' writing skills significantly. This improvement can be seen from various aspects, such as the use of better grammar, richer vocabulary, and more regular essay structures. Apart from that, the TPS model also encourages active student participation in the learning process, increases interaction between students, and creates a more collaborative and enjoyable learning atmosphere. Thus, the TPS learning model can be considered effective in improving students' Arabic essay writing skills. This research recommends using the TPS model as an alternative learning strategy to improve students' writing skills.